2015
DOI: 10.1111/nan.12249
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the lateral geniculate nucleus in Alzheimer's disease but not dementia with Lewy bodies

Abstract: AimsComplex visual hallucinations occur in 70% of dementia with Lewy bodies (DLB) cases and significantly affect patient well‐being. Visuo‐cortical and retinal abnormalities have been recorded in DLB and may play a role in visual hallucinations. The present study aimed to investigate the lateral geniculate nucleus (LGN), a visual relay centre between the retina and visual cortex, to see if changes to this structure underlie visual hallucinations in DLB.MethodsFifty‐one [17 probable DLB, 19 control and 15 proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…Pathology of the lateral geniculate nucleus showed no significant differences between DLB with VH and AD. However, AD cases had significantly more Aβ, less parvocellular neurons and had magnocellular gliosis compared to controls and DLB . Results from the study of the superior colliculus showed reduced neuronal densities in DLB in the stratum griseum intermedium compared to AD and controls .…”
Section: Methodsmentioning
confidence: 89%
“…Pathology of the lateral geniculate nucleus showed no significant differences between DLB with VH and AD. However, AD cases had significantly more Aβ, less parvocellular neurons and had magnocellular gliosis compared to controls and DLB . Results from the study of the superior colliculus showed reduced neuronal densities in DLB in the stratum griseum intermedium compared to AD and controls .…”
Section: Methodsmentioning
confidence: 89%
“…By contrast, the superior colliculus and the parietal and frontal cortex play an essential role in gaze fixation. There is evidence that both the geniculate body and the superior colliculus are affected by AD [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological and physiological studies have demonstrated changes in the retina in DLB. However, the lateral geniculate nucleus (LGN), the primary afferent visual relay structure between the retina and the primary visual cortex, is spared in DLB compared with AD, suggesting that visual hallucinations in DLB may be facilitated by pathological changes in other parts of the visual system. In contrast to the LGN, α‐synuclein pathology was found throughout the pulvinar but was particularly marked in the medial pulvinar.…”
Section: Discussionmentioning
confidence: 99%
“…Images were taken within the dissector frames and analyzed using an ImagePro Plus v.4.1 image analysis system (Media Cybernetics, Bethesda, MD. Using previously published techniques, the mean percentage area of immunopositivity was determined by standardizing red‐green‐blue thresholds per antibody and applying these to all sections per case. Each case thus had a mean value generated per antibody across all sections analyzed.…”
Section: Methodsmentioning
confidence: 99%